Association of low serum vitamin D level among pulmonary tuberculosis patients - Bansiwal, Babulal; Phulwari, Jitendra; Saxena, Anil; A., Shinu (International Journal of Research in Medical Sciences, 2020)
Background: Recent studies suggest that the incidence and severity of tuberculosis is associated with low levels of Vitamin D, this is especially important in developing countries like India which carries a major portion of global Tuberculosis burden. Therefore, this study aimed to determine the prevalence of Vitamin D deficiency in newly diagnosed tuberculosis patients in our institute. Aims and objective is to study the deficiency of Vitamin D In newly diagnosed sputum positive pulmonary TB and to compare the level of Vitamin d with that of age matched healthy control population. Methods: This was a descriptive cross-sectional case control study to asses Vitamin D deficiency among 140 cases which included 2 categories of patients (a) Group 1: 70 sputum AFB positive newly diagnosed pulmonary TB patients, (b) Group 2: 70 apparently healthy people who came to the hospital with regular checkup. Results: Mean age of study groups and control in years were, Control: 40.3857±10.231, Cases: 36.885±11.076. Mean BMI was significantly higher in controls when compared with new TB cases (19.27±2.455 vs 15.215±1.774) kg/m2 p <0.05). There was significant decrease in mean Vitamin D3 value when new cases TB patients were compared with controls (18.212±9.3027 vs 36.1267±8.410 p <0.05). Conclusions: Patients with tuberculosis are significantly Vitamin D deficient as compared to normal people. This deficiency is more marked in females and those with low BMI. The present finding favours the role of Vitamin D in the prevention and treatment of tuberculosis in developing countries like India.